2021
DOI: 10.21580/at.v13i1.8151
|View full text |Cite
|
Sign up to set email alerts
|

Student Science Process Skills through the Application of Computer Based Scaffolding assisted by PhET Simulation

Abstract: Basic physics practicum learning through virtual laboratories is less than optimal in developing students' science process skills. This study reveals the results of improving students' science process skills based on the application of computer scaffolding assisted by PhET simulation. This study uses a quantitative approach with a sample of 14 students through purposive sampling technique. The research stages consist of introduction, implementation, and evaluation. Collecting data through interviews, tests, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…This study posits that the combination of three concepts (i.e., Computer-based scaffolding, AI, and scientific writing) can improve the quality of STEM education and change teachers' perceptions toward using educational technology in their STEMrelated classrooms. Several existing studies have demonstrated that computer-based scaffolding is effective in improving students' advanced problem-solving and higher-order thinking skills in STEM education (González-Gómez and Jeong, 2019;Kim et al, 2021;Saputri, 2021). This is because computer-based scaffolding of cognitive, metacognitive, and strategic supports can address students' needs and learning difficulties during the learning process of solving the ill-structured/authentic STEM-related tasks (Belland et al, 2017).…”
Section: Artificial Intelligence Scaffolding For Scientific Writing I...mentioning
confidence: 99%
“…This study posits that the combination of three concepts (i.e., Computer-based scaffolding, AI, and scientific writing) can improve the quality of STEM education and change teachers' perceptions toward using educational technology in their STEMrelated classrooms. Several existing studies have demonstrated that computer-based scaffolding is effective in improving students' advanced problem-solving and higher-order thinking skills in STEM education (González-Gómez and Jeong, 2019;Kim et al, 2021;Saputri, 2021). This is because computer-based scaffolding of cognitive, metacognitive, and strategic supports can address students' needs and learning difficulties during the learning process of solving the ill-structured/authentic STEM-related tasks (Belland et al, 2017).…”
Section: Artificial Intelligence Scaffolding For Scientific Writing I...mentioning
confidence: 99%
“…Aspek membuat hipotesis menjadi aspek yang paling rendah peningkatannya. Saputri (2021) menyebutkan bahwa merumuskan hipotesis merupakan indikator penting karena melibatkan peserta didik memikirkan hubungan dan keterkaitan antar variable yang diuji melalui praktikum (Maison, dkk: Kurangnya pemahaman tentang variabel dalam praktikum membuat mahasiswa memiliki kemampuan hipotesis yang kurang optimal sehingga pendidik perlu menekankan tentang variabel-variabel yang ada dalam sebuah eksperimen.…”
Section: Hasil Dan Pembahasanunclassified
“…This includes developing general investigative skills (such as posing and pursuing open-ended questions, synthesizing information, planning and conducting experiments, analyzing, and presenting results). For example, during classroom lessons, students were engaged in tasks such as making observations and inferences, planning experiments, and generating predictions (Abungu et al, 2014., Chebii et al, 2012, Rauf et al 2013, Saputri, 2021. As a consequence of involving students in these learning activities, they work collaboratively in groups, interact with each other through discussion and carrying out experiments under the guidance of the teacher.…”
Section: The Importance Of Instructional Activities and Development O...mentioning
confidence: 99%
“…It enables students to communicate their results but also to improve their communicative skills in interpreting what they have observed through words, graphs, or tables and drawing their own conclusions depending on the patterns or relationship of their results. In addition, Rauf et al (2013) and Saputri (2021) explained that when students are involved in a discursive process, their science process skills become more developed. However, the studies are based on biological and physics phenomena rather than the current, which is based on chemistry, particularly chemical kinetics, equilibrium, and energetics.…”
Section: Evidence From Students Workmentioning
confidence: 99%